Inflammation mediates the relationship between cardiometabolic index and vulnerable plaque in patients with acute coronary syndrome - Haihao Yan; Sai Lv; Haiyao Pi; Haixu Yu; Weijun Yin; Yaran Wang; Yonghao Lan; Wei Liu (Lipids in Health and Disease)
Abstract Background As a novel indicator reflecting metabolic status and visceral adiposity distribution, the cardiometabolic index (CMI) has gained attention in cardiovascular risk stratification. This investigation employed optical coherence tomography (OCT) to examine potential associations between CMI and vulnerable plaque, as well as the role of inflammation. Methods This study conducted a cross-sectional analysis of 270 acute coronary syndrome (ACS) patients who had OCT imaging evaluation. Patients were categorized based on CMI tertiles, with CMI calculated using the formula [waist (cm)/height (cm)]×[triglycerides (mmol/L)/HDL-C (mmol/L)]. OCT was used to assess plaque events in culprit lesions and plaque components in non-culprit lesions, and inflammatory markers were measured. A mediation analysis framework was implemented to investigate inflammatory pathways in CMI-vulnerable plaque relationships. Results CMI tertiles were linked to vulnerable plaque traits: thin-cap fibroatheromas (TCFA), macrophages (Tertiles1 vs. Tertiles2 vs. Tertiles3, TCFA: 10.0% vs. 20.0% vs. 26.7%, P = 0.016; macrophages: 17.8% vs. 28.9% vs. 36.7%, P = 0.019). Multivariate regression demonstrated CMI elevation independently predicted a higher prevalence of TCFA (OR:1.40, 95%CI: 1.25–2.89, P = 0.003), more macrophage infiltration (OR:1.61, 95% CI:1.09–2.37, P = 0.017), reduced FCT (β:-30.65, 95% CI:-50.72-10.57, P = 0.003), and enlarged maximum lipid arc (β:20.78, 95% CI:6.55–35.01, P = 0.004). Moreover, CMI was positively related to hsCRP, WBC, and neutrophils. Mediation analysis revealed that hsCRP mediated about 17.0% of the association between CMI and minimum FCT [Indirect effect=-5.21, 95% CI=(-12.70, -1.27), P = 0.016]. Conclusions CMI is a key forecaster of vulnerable plaque in patients with ACS. Systemic inflammation is associated with the relationship between CMI and vulnerable plaque features, suggesting a potential mechanistic link.